Detection of Mosaic Variants in Mothers of MPS II Patients by Next Generation Sequencing - Oliveira Netto, Alice Brinckmann; Brusius-Facchin, Ana Carolina; Leistner-Segal, Sandra; Kubaski, Francyne; Josahkian, Juliana; Giugliani, Roberto (Frontiers in Molecular Biosciences, 2021)
Mucopolysaccharidosis type II is an X-linked lysosomal storage disorder caused by mutations in the IDS gene that encodes the iduronate-2-sulfatase enzyme. The IDS gene is located on the long arm of the X-chromosome, comprising 9 exons, spanning approximately 24 kb. The analysis of carriers, in addition to detecting mutations in patients, is essential for genetic counseling, since the risk of recurrence for male children is 50%. Mosaicism is a well-known phenomenon described in many genetic disorders caused by a variety of mechanisms that occur when a mutation arises in the early development of an embryo. Sanger sequencing is limited in detecting somatic mosaicism and sequence change levels of less than 20% may be missed. The Next Generation Sequencing (NGS) has been increasingly used in diagnosis. It is a sensitive and fast method for the detection of somatic mosaicism. Compared to Sanger sequencing, which represents a cumulative signal, NGS technology analyzes the sequence of each DNA read in a sample. NGS might therefore facilitate the detection of mosaicism in mothers of MPS II patients. The aim of this study was to reanalyze, by NGS, all MPS II mothers that showed to be non-carriers by Sanger analysis. Twelve non-carriers were selected for the reanalysis on the Ion PGM and Ion Torrent S5 platform, using a custom panel that includes the IDS gene. Results were visualized in the Integrative Genomics Viewer (IGV). We were able to detected the presence of the variant previously found in the index case in three of the mothers, with frequencies ranging between 13%-49% of the reads. These results suggest the possibility of mosaicism in the mothers. The use of a more sensitive technology for detecting low-level mosaic mutations is essential for accurate recurrence-risk estimates. In our study, the NGS analysis showed to be an effective methodology to detect the mosaic event.